2016
DOI: 10.2217/bmm-2016-0165
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Biomarker Value of Binary and Grayscale Breast Tumor Histopathology Images

Abstract: The critical prognostic importance of the grayscale texture is revealed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…This result was not expected in view of the fact that multifractal analysis was particularly designed for improved analysis of irregular natural forms with their typically uneven distribution of complexity. Our previous study has indicated a comparable prognostic value of monofractal and multifractal analyses of pan-tissue stained breast tumor tissue sections (28). …”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…This result was not expected in view of the fact that multifractal analysis was particularly designed for improved analysis of irregular natural forms with their typically uneven distribution of complexity. Our previous study has indicated a comparable prognostic value of monofractal and multifractal analyses of pan-tissue stained breast tumor tissue sections (28). …”
Section: Discussionmentioning
confidence: 94%
“…This was striking in view of the fact that intensity quantification is the standard approach to immunostaining evaluation, while fractal analysis is mainly considered as a method of choice for pan-tissue staining. We have previously conducted a fractal analysis of the pan-tissue H&E stained tumor histopathology specimens for the prognostic purpose (24, 28). Fractal analysis thereby performed far better on grayscale then on binary images (28) which directly opposed the results obtained in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The invasive breast cancer (BC) and inflammatory breast cancer (IBC) patient groups used in this study have been previously described in full detail, together with their power calculations for unprocessed images (Rajkovic et al ., 2016a,b). The targeted effect size by hazard ratio, variability (in standard deviations) and the event rate are essential parameters for the calculation of sample size needed for Cox regression.…”
Section: Methodsmentioning
confidence: 99%
“…This rationale is based on the hypothesis that such images contain distributed prognostic information which remain unused by either visual or computational evaluations targeting specific structures. There have been several previous reports utilising this approach for prognostic purposes (Tambasco & Magliocco, ; Tambasco et al ., ; Vujasinovic et al ., ; Kolarevic et al ., ; Rajkovic et al ., 2016a,b; Mezheyeuski et al ., ). Such unselective approach to histopathology image analysis has a potential for routine clinical application as it often outperforms the major molecular prognostic tools such as multiplex ELISA (Jia et al ., ) and gene expression microarrays (Buyse et al ., ).…”
Section: Introductionmentioning
confidence: 99%